Cell-mediated immunity in HIV seronegative patients recovered from Cryptococcus neoformans var. gattii meningitis. - Seaton, R; Naraqi, S; Wembri, J; Warrell, D (1997)
Cell-mediated immunity was assessed in 37 HIV seronegative healthy patients cured of Cryptococcus neoformans var. gattii meningitis and compared with matched controls using a multitest device which simultaneously injects seven standardized common antigens intradermally. Responses in patients and controls were similar: however, male patients had significantly higher compound (average) scores than controls (P = 0.041). Male scores were higher than female scores in both patient (P = 0.002) and control (P = 0.017) groups. In eight patients with acute cryptococcal meningitis, seven were anergic to challenge with 5 IU of tuberculin on admission. Two of these patients had positive reactions after treatment. Three of four patients tested prior to treatment with the multitest device were anergic to all seven antigens but all three survivors showed improved responsiveness following cure. These data suggest that patients are immunosuppressed on presentation (due to overwhelming var. gattii infection) but that following cure, cell-mediated immunity improves to its premorbid state. A transient state of immunosuppression prior to the development of the disease cannot be excluded.